EXPERIENTIAL LEARNING: UTILIZING LOCAL WISDOM OF NIAS FOR FUTURE GENERATIONS - Harefa, Darmawan; Putu Budi Adnyana; I Gede Astra Wesnawa; I Putu Wisna Ariawan (Civic Society Research and Education: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2024)
This study aims to explore the implementation of experiential learning that utilizes the local wisdom of Nias in education. The method used is qualitative with a case study approach, involving interviews and observations in several schools in Nias. The results indicate that the integration of local wisdom in the learning process can enhance student motivation and engagement, as well as strengthen their understanding of cultural identity. However, this research also identifies challenges, such as limited resources and insufficient training for teachers. The conclusion of this study emphasizes the importance of leveraging local wisdom to create a generation that is not only academically intelligent but also proud of their culture. Recommendations include enhancing teacher training and developing relevant educational resources.